2014
DOI: 10.1002/ajhb.22673
|View full text |Cite
|
Sign up to set email alerts
|

Ontogenetic changes in cranial vault thickness in a modern sample of Homo sapiens

Abstract: The pattern of thickness arrangement is established early in ontogeny but CVT increases and changes in distribution until adolescence. Several factors may influence CVT, such as the brain, muscles, vessels, and sutures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
31
0
5

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 60 publications
(100 reference statements)
4
31
0
5
Order By: Relevance
“…In their second study, the parietal boss was recognized as the thickest while the posterior inferior part was the thinnest (Peterson and Dechow, ). Anzelmo et al () identified the thickest regions of the parietal bone along the midline in the upper parts of the bone, while the thinnest regions appear to be the lateral walls and the lower parts of the cranial bones. These findings are in agreement with the results of the present study, in which the upper parts tend to be thicker, while the lower parts of the parietal bone tend to be thinner.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In their second study, the parietal boss was recognized as the thickest while the posterior inferior part was the thinnest (Peterson and Dechow, ). Anzelmo et al () identified the thickest regions of the parietal bone along the midline in the upper parts of the bone, while the thinnest regions appear to be the lateral walls and the lower parts of the cranial bones. These findings are in agreement with the results of the present study, in which the upper parts tend to be thicker, while the lower parts of the parietal bone tend to be thinner.…”
Section: Discussionmentioning
confidence: 99%
“…Skrzat et al () observed some differences in the diploe density of younger and older adults due to a reduction in calcium concentration. No significant sexual differences have been described in CVT (Ross et al, ; Lynnerup, ; Lynnerup et al, ; Torres‐Lagares et al, ; Sabancıoğulları et al, ; Anzelmo et al, ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the profuse number of investigations regarding the cranium microstructure and histology using noninvasive-nondestructive analytical protocols, such as scanning electron microscope (SEM) (Kranioti et al, 2009;Martínez-Maza, 2007;Martínez-Maza et al, 2006, 2011Mowbray, 2005), computed tomography (CT) (Anzelmo et al, 2014), micro-computed tomography (CT) (Rühli et al, 2007) and synchrotron absorption-based CT (Sanchez et al, 2012), conventional histological techniques used to assess bone tissue through bone thin sections (e.g., Enlow, 1968), could aid in better understanding human cranium ontogeny and the evolution of the cranium (Bartsiokas, 2002;Martínez-Maza et al, 2006). The present study focused on the histological analysis of cranial vault bones, in which we explored the microstructure of the frontal, parietal and occipital bones of three individuals from the same osteoachaeological collection with different ages (child, adolescent and young adult).…”
Section: Introductionmentioning
confidence: 99%
“…Compared to normal anatomical variations of the vault thickness [11,14,16], the pronounced asymmetry of the parietal bones and the marked thinning of the parasagittal posterior part of the parietal bones suggested pressure exerted from above by a headdeforming device, while the lack of regular occipital thickening anteroposteriorly towards the external occipital protuberance suggested pressure exerted from behind by a headdeforming device.…”
Section: Discussionmentioning
confidence: 98%